Corporate Social Responsibility dan Zakat Perusahaan dalam Perspektif Hukum Ekonomi Islam - A. Chairul Hadi (AHKAM : Jurnal Ilmu Syariah, 2016)
Corporate Social Responsibility and Zakat of Company in the Perspective of Islamic Economic Law. Awareness of social responsibility by companies (corporate social responsibility) is increasing today. Almost every company has a board focusing on social services. In the Islamic banking industry, this social responsibility gets serious attention. The study revealed that besides allocating social funds, Islamic banks allocate funds for zakat of company as an obligation of a legal entity (syakhshiyyah hukmiyyah).DOI: 10.15408/ajis.v16i2.4453